Carbon Nanotubes and Their Applications - Zhang, Qing, editor 553553 (Singapore : Pan Stanford Publishing Pte. Ltd., 2012)
This book overviews the current status of research and development activities of CNTs in nanodevices, nanomaterials, or nanofabrication. This book presents 15 state-of-the-art review articles that cover CNT synthesis technologies for growing highly orientated CNTs, chirality-pure CNTs and CNTs at a large throughput and low cost, CNT assembly techniques, CNT sorting and separation processes, CNT functionalization engineering for more functionalities, CNT fundamental properties and their practical/potential electrical, electronic, optical, mechanical, chemical and biological applications.